Membangun Jalur Komunikasi Antara Darat Dengan Laut Via VSAT - Deni Kurniawan; Ismail Ismail (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2024)
PT. Bintang Khatulistiwa Internusa is one of the vendors engaged in providing infrastructure and internet services specifically for ships. Customers who sail often need internet services to transmit data and communicate with the head office in Jakarta, so it is necessary to develop communication infrastructure that can connect between land and sea, this is an important challenge in the current era of digitalization. Visat, a technology that utilizes satellites to transfer data, has emerged as a potential solution for creating effective and reliable communication lines. This study aims to explore the process of building communication lines via Vsat that connect land and sea. Through literature analysis and case studies, PT. Bintang Khatulistiwa Internusa takes advantage of Visat technology in overcoming the geographic and infrastructure challenges associated with building communications lines in hard-to-reach areas. We also consider the economic, social, and environmental implications of implementing this technology. The results show that Vsat has great potential to improve connectivity between land and sea, providing significant benefits in terms of economic growth, regional integration and availability of access to information. However, challenges such as implementation costs, data security, and infrastructure resilience remain major concerns that need to be addressed in efforts to implement communication channels through Visat. Thus, this research provides important insights for stakeholders to plan and implement more efficient and inclusive communications infrastructure in land and sea areas.